Negative Pressure Neurogenesis: A Novel Approach to Accelerate Nerve Regeneration after Complete Peripheral Nerve Transection. Issue 5 (May 2021) - Mettyas, Tamer; Barton, Matthew; Sahar, Muhammad Sana Ullah; Lawrence, Felicity; Sanchez-Herrero, Alvaro; Shah, Megha; St John, James; Bindra, Randy
Abstract : Background: Various modalities to facilitate nerve regeneration have been described in the literature with limited success. We hypothesized that negative pressure applied to a sectioned peripheral nerve would enhance nerve regeneration by promoting angiogenesis and axonal lengthening. Methods: Wistar rats' sciatic nerves were cut (creating 7 mm nerve gap) and placed into a silicone T-tube, to which negative pressure was applied. The rats were divided into 4 groups: control (no pressure), group A (low pressure: 10 mm Hg), group B (medium pressure: 20/30 mm Hg) and group C (high pressure: 50/70 mm Hg). The nerve segments were retrieved after 7 days for gross and histological analysis. Results: In total, 22 rats completed the study. The control group showed insignificant nerve growth, whereas the 3 negative pressure groups showed nerve growth and nerve gap reduction. The true nerve growth was highest in group A (median: 3.54 mm) compared to group B, C, and control (medians: 1.19 mm, 1.3 mm, and 0.35 mm); however, only group A was found to be significantly different to the control group (** P < 0.01). Similarly, angiogenesis was observed to be significantly greater in group A (** P < 0.01) in comparison to the control. Conclusions: Negative pressure stimulated nerve lengthening and angiogenesis within an in vivo rat model. Low negative pressure (10 mm Hg) provided superior results over the higher negative pressure groups and the control, favoring axonal growth. Further studies are required with greater number of rats and longer recovery time to assess the functional outcome.